2023
DOI: 10.1111/tpj.16461
|View full text |Cite
|
Sign up to set email alerts
|

The P1 protein of wheat yellow mosaic virus exerts RNA silencing suppression activity to facilitate virus infection in wheat plants

Dao Chen,
Hui‐Ying Zhang,
Shu‐Ming Hu
et al.

Abstract: SUMMARYWheat yellow mosaic virus (WYMV) causes severe wheat viral disease in Asia. However, the viral suppressor of RNA silencing (VSR) encoded by WYMV has not been identified. Here, the P1 protein encoded by WYMV RNA2 was shown to suppress RNA silencing in Nicotiana benthamiana. Mutagenesis assays revealed that the alanine substitution mutant G175A of P1 abolished VSR activity and mutant Y10A VSR activity remained only in younger leaves. P1, but not G175A, interacted with gene silencing‐related protein, N. be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…It was recently found that RNA silencing can be regulated by the signal cascade of calmodulin (CaM) protein binding with calmodulin-binding transcription activator 3 (CAMTA3) protein; the CaM– CAMTAs interaction upregulates transcription of RNA-silencing related genes such as those encoding dicer1 (DCL1), bifunctional nuclease 2 (BN2), Argonaute protein (AGO), and RNA-dependent RNA polymerase 6 (RDR6), which enhance the resistance of Nicotiana benthamiana plants (Wang et al, 2021; Wang et al, 2022). Our laboratory research showed that WYMV P1 protein also has viral suppressor of RNA silencing (VSR) activity, and plays a suppressor role by interfering with calmodulin-related antiviral RNAi defense, confirming that its VSR activity contributes to the systemic infection of WYMV in wheat (Chen et al, 2023). The P2 proteins of BaMMV, OMV, and BaYMV may be related to fungal transmission (Jacobi et al, 1995; Peerenboom et al, 1992; Zheng et al, 2002).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…It was recently found that RNA silencing can be regulated by the signal cascade of calmodulin (CaM) protein binding with calmodulin-binding transcription activator 3 (CAMTA3) protein; the CaM– CAMTAs interaction upregulates transcription of RNA-silencing related genes such as those encoding dicer1 (DCL1), bifunctional nuclease 2 (BN2), Argonaute protein (AGO), and RNA-dependent RNA polymerase 6 (RDR6), which enhance the resistance of Nicotiana benthamiana plants (Wang et al, 2021; Wang et al, 2022). Our laboratory research showed that WYMV P1 protein also has viral suppressor of RNA silencing (VSR) activity, and plays a suppressor role by interfering with calmodulin-related antiviral RNAi defense, confirming that its VSR activity contributes to the systemic infection of WYMV in wheat (Chen et al, 2023). The P2 proteins of BaMMV, OMV, and BaYMV may be related to fungal transmission (Jacobi et al, 1995; Peerenboom et al, 1992; Zheng et al, 2002).…”
Section: Introductionmentioning
confidence: 69%
“…The qRT-PCR results showed that the gene for CaM was the most significantly downregulated; it was recently reported that VSRs exert suppressor activity by directly interacting with CaM, thereby interfering with the CaM–CAMTA3 interaction (Chen et al, 2023; Wang et al, 2021; Wang et al, 2022). Therefore, Y2H and BiFC were used to verify the P2–CaM interaction (Figure 3; Supporting Figure 7).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations